2020
DOI: 10.1080/01691864.2020.1769724
|View full text |Cite
|
Sign up to set email alerts
|

Can a humanoid robot continue to draw attention in an office environment?

Abstract: This study focuses on the use of humanoid robots in office environments, and investigates whether a robot can maintain the attention of passersby after initiation of face-to-face contact. Drawing attention can be considered as a first step in improving the continuity of use of robots; such continuity is one factor in validating their social acceptance, which must be considered when disseminating robots in offices. In this study, we assume that the robot approaches and greets users in order to make the users aw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 52 publications
2
2
0
Order By: Relevance
“…In addition, the results of the previous studies indicated that men have a more positive attitude toward interacting with robots than women [ 37 , 38 ]. However, other studies that use the robot “Sota,” which is the same as used in the present study, [ 39 ] showed that women are more interested in the robot; this finding is consistent with our results. Therefore, the results suggest that biological sex difference in terms of the interest in the robots does not give a definite decision, but it may depend on the appearance of the robot.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In addition, the results of the previous studies indicated that men have a more positive attitude toward interacting with robots than women [ 37 , 38 ]. However, other studies that use the robot “Sota,” which is the same as used in the present study, [ 39 ] showed that women are more interested in the robot; this finding is consistent with our results. Therefore, the results suggest that biological sex difference in terms of the interest in the robots does not give a definite decision, but it may depend on the appearance of the robot.…”
Section: Discussionsupporting
confidence: 93%
“…Finally, it was determined that, when pedestrians are in a group, they are more likely to stop and are more willing to listen to the full message. Several examples of these observations have been reported in other studies [ 17 , 24 , 26 , 39 ]. These observations were thought to be caused by another person who draws the pedestrian to interact with the robot, and not by the robot itself [ 17 , 24 ].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In face-to-face conversations, individuals would look at their partner's eyes, mouth, or face to retrieve information about the speech contents, emotions, and attitudes (Degutyte & Astell, 2021). With regard to robots, their speech could effectively catch people's visual attention to initiate communications (Okafuji et al, 2020). A publicly speaking Pepper robot could maintain the attention of audiences when the audiences are interested in the speech (Bourguet, Xu, Zhang, Urakami, & Venture, 2020).…”
Section: Voice Human-likenessmentioning
confidence: 99%